PENGARUH FINFLUENCER DAN FOMO TERHADAP MINAT INVESTASI SAHAM GENERASI Z INDONESIA - Magfirah Wahyu Ramadhani; Nurul Chalisa Majiding; Sri Utami (Journal of Financial Economics & Investment, 2026)
This study aims to analyze the influence of finfluencers and Fear of Missing Out (FOMO) on the stock investment interest of Indonesian Generation Z. This issue is important because the increasing use of social media as a source of investment information can shape investment interest, but also has the potential to drive decisions influenced by trends and social pressure. This study employs a quantitative approach using a survey design. Primary data was collected via a Likert-scale questionnaire administered to 150 Generation Z respondents who are aware of or follow investment content on social media. The data was analyzed using validity, reliability, correlation, and multiple linear regression tests. The results indicate that finfluencers have a positive and significant effect on stock investment interest. FOMO also has a positive and significant effect on interest in stock investment. Simultaneously, finfluencers and FOMO can explain variations in interest in stock investment. These findings indicate that finfluencers and the psychological driver known as FOMO play a crucial role in shaping Generation Z’s interest in stock investment. This study contributes to the development of behavioral finance research regarding Generation Z’s investment behavior in the digital era.